2017
DOI: 10.1155/2017/3242301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Total Glucosides of Paeony for Primary Sjögren’s Syndrome: A Systematic Review

Abstract: Objective To evaluate the clinical efficacy and safety of total glucosides of paeony (TGP) for primary Sjögren's syndrome (pSS). Methods Eight electronic databases were searched from their inception to July 2016. Clinical randomized controlled trials (RCTs) were included. The study quality was evaluated according to the standard suggested in the Cochrane Handbook. RevMan 5.1 was used for statistical analysis. Results Seven RCTs involving 443 patients were included. The results showed that TGP combined with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…17 A systemic review showed that TGP combined with an immunosuppressant (IS) was superior to IS alone in the treatment of pSS. 18 However, high-quality randomized controlled trials are needed to confirm the therapeutic effects of TGP.…”
Section: Discussionmentioning
confidence: 99%
“…17 A systemic review showed that TGP combined with an immunosuppressant (IS) was superior to IS alone in the treatment of pSS. 18 However, high-quality randomized controlled trials are needed to confirm the therapeutic effects of TGP.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, only one systematic review regarding the effectiveness and safety of TGP in the treatment of pSS has been reported (Jin et al, 2017). However, this review only included articles until July 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above modern pharmacological evidence, TGP can be administrated in various autoimmune disorders. In addition to RA, TGP have been commonly prescribed for diseases of ankylosing spondylitis, primary Sjogren’s syndrome, oral lichen planus, and alopecia areata 2832…”
Section: Discussionmentioning
confidence: 99%